Tertiary wastewater treatment in membrane photobioreactor using microalgae: Comparison of forward osmosis & microfiltration. (December 2016) - Praveen, Prashant; Heng, Jonathan Yun Ping; Loh, Kai-Chee
Highlights: Forward osmosis and microfiltration based membrane photobioreactors were operated. Bioreactors exhibited excellent N and P removal efficiency. Membrane rejection played important role in osmotic membrane photobioreactor. More than 2 g/L microalgae were accumulated in the bioreactor. Operating costs for FO-based system was 32–45% higher. Abstract: Discharge of wastewater with high nitrogen and phosphorus content is a major cause of eutrophication. In this study, a microfiltration-based membrane photobioreactor (MPBR) and forward osmosis-based osmotic membrane photobioreactor (OMPBR) have been operated with Chlorella vulgaris for continuous tertiary wastewater treatment. Both the bioreactors exhibited good biomass accumulation (over 2 g/L), although the OMPBR achieved better nutrients removal due to high rejection properties of the membranes. At 2 days HRT, the OMPBR achieved nitrogen and phosphorus removal efficiencies of 86–99% and 100%, respectively, whereas the corresponding values in the MPBR were 48–97% and 46%, respectively. Based on the energy input, the total operating costs for OMPBR were 32–45% higher than that of the MPBR, and filtration cost for OMPBR was 3.5–4.5 folds higher than that of the MPBR. These results indicate that the integration of membrane filtration with photobioreactors is promising in microalgae-based tertiary wastewater treatment.